ANALYSIS OF SENTENCE USE IN WHATSAPP CHAT BETWEEN LECTURERS AND STUDENTS - Ertinawati, Yuni; Rahmawati, Kania Dwi; Mutiara, Naila Hanum; Nurmerisa, Ribi Sabina (Media Inovasi Pendidikan dan Publikasi, 2024)
This research was motivated by the author's interest in the problems of students in the RMIK 1A study program regarding the use of sentences in WhatsApp chats between lecturers and students. As communication develops in the digital era, the use of social media has become a common need for everyone, one of which is WhatsApp as a semi-formal communication tool. WhatsApp not only makes it easier to exchange information, but also influences the way messages are delivered and language is used. Using WhatsApp in academic communications offers various advantages, including ease of access, speed of response, and flexibility in communication. The language used must pay attention to the rules of good grammar, spelling and politeness. Analyzing language use errors can help in developing students' language skills. This can improve communication skills in Indonesian and correct mistakes that often occur. From an ethical perspective, this research can help in evaluating digital interactions in compliance with applicable academic norms. This can contribute to increasing digital literacy for both lecturers and students, helping to optimize the use of technology in academic interactions.